2016
DOI: 10.1016/j.semarthrit.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Calcinosis is associated with digital ulcers and osteoporosis in patients with systemic sclerosis: A Scleroderma Clinical Trials Consortium study

Abstract: Objectives We sought to identify the clinical factors associated with calcinosis in an international multicenter collaborative effort with the Scleroderma Clinical Trials Consortium (SCTC). Methods This is a retrospective cohort study of 5218 patients with systemic sclerosis (SSc). Logistic regression was used to obtain odds ratios (OR) relating calcinosis to various clinical features in multivariate analyses. Results A total of 1290 patients (24.7%) had calcinosis. In univariate analyses, patients with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 27 publications
(36 reference statements)
4
43
0
6
Order By: Relevance
“…On the other hand, the higher prevalence of calcinosis in the Cairns cohort, also thought to be a long‐term consequence of digital ischemia, argues against the possibility that the lower prevalence of digital ulcers is due to shorter disease duration or less cold‐induced ischaemia in the Cairns cohort . This is also out of keeping with the findings of a previous multi‐centre cohort study, which found a strong association of calcinosis with digital ulcers, in cohorts from temperate areas around the world, including Canada and the United Kingdom . Hence, while some disease features may be ameliorated by living in the tropics, the prevalence of other features, such as calcinosis, is not affected by the warmer climate.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, the higher prevalence of calcinosis in the Cairns cohort, also thought to be a long‐term consequence of digital ischemia, argues against the possibility that the lower prevalence of digital ulcers is due to shorter disease duration or less cold‐induced ischaemia in the Cairns cohort . This is also out of keeping with the findings of a previous multi‐centre cohort study, which found a strong association of calcinosis with digital ulcers, in cohorts from temperate areas around the world, including Canada and the United Kingdom . Hence, while some disease features may be ameliorated by living in the tropics, the prevalence of other features, such as calcinosis, is not affected by the warmer climate.…”
Section: Discussionsupporting
confidence: 75%
“…We previously reported in a multicenter international cohort of 7,056 SSc patients an overall frequency of calcinosis of 22%. We also demonstrated that patients with calcinosis had longer mean disease duration from the first non–Raynaud's phenomenon symptom than those without .…”
Section: Introductionmentioning
confidence: 55%
“…Valenzuela i wsp. zaobserwowali u tych pacjentów zwiększone ryzyko wystąpienia owrzodzeń opuszek palców, a także zajęcia układu krążenia oraz układu pokarmowego i oddechowego [7]. Wyniki badań kohortowych potwierdzają również statystycznie częst-sze występowanie zaburzeń kostnych i wapnienia tkanek u osób, u których stwierdzono przeciwciała antycentromerowe (ACA), niż u osób z przeciwciałami przeciwko topoizomerazie I (Scl-70) [7].…”
Section: Omówienieunclassified
“…trzeszczenie stawów, które spowodowane jest zmianami w obrębie ścięgien (objaw tarcia ścięgien). Ponadto u większości osób z SSc w badaniu rentgenograficznym (RTG) kość-ca opisuje się odkładanie złogów wapnia zarówno w okolicach okołostawowych, jak i w innych lokalizacjach [5][6][7]. Resorpcja kostna dystalnych paliczków dłoni opisywana jest rzadko, jednak uważa się, że może występować nawet u ponad 25% chorych na SSc [6], co przyczynia się do stopniowego zaniku kostnego, a w przypadkach skrajnych nawet do cał-kowitej resorpcji kości.…”
unclassified